Time-Resolved Spectroscopy of Organometallic Alkane and Silane Intermediates - Bowman, Edward (2024)
Chapter 1 In this Chapter, the history of time-resolved spectroscopic methods is reviewed, with particular focus on IR spectroscopy and XAS spectroscopy. The study of metal carbonyl intermediates, the family of complexes investigated in this Thesis, and the previous investigation of their photochemistry is also reviewed.